Next Generation DNA Led Technologies - Avadhanam, Sharada; Jyothsna, G.; Kashyap, Amita (SpringerBriefs in Forensic and Medical Bioinformatics, 2016)
This brief highlights advances in DNA technologies and their wider applications. DNA is the source of life and has been studied since a generation, but very little is known as yet. Several sophisticated technologies of the current era have laid their foundations on the principle of DNA based mechanisms. DNA based technologies are bringing a new revolution of Advanced Science and Technology. Forensic Investigation, Medical Diagnosis, Paternity Disputes, Individual Identity, Health insurance, Motor Insurance have incorporated the DNA testing and profiling technologies for settling the issues.